2015
DOI: 10.1007/s10397-015-0883-7
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linked xenogenic collagen implantation in the sheep model for vaginal surgery

Abstract: The properties of meshes used in reconstructive surgery affect the host response and biomechanical characteristics of the grafted tissue. Whereas durable synthetics induce a chronic inflammation, biological grafts are usually considered as more biocompatible. The location of implantation is another determinant of the host response: the vagina is a different environment with specific function and anatomy. Herein, we evaluated a cross-linked acellular collagen matrix (ACM), pretreated by the anti-calcification p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Lastly, the ovine levator ani muscle retracts the anus yet not truly supporting pelvic organs, Gynecol Obstet Invest 2017;82:582-591 DOI: 10.1159/000454771 590 which rest rather on the bony pelvic floor. Our dissections confirmed the presence of extravaginal spaces of relevance to surgical experimentation [10][11][12]. Given the different urethral insertion point, dissection of the ventral vaginal wall is more difficult in its lower part, yet feasible above the urethra.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…Lastly, the ovine levator ani muscle retracts the anus yet not truly supporting pelvic organs, Gynecol Obstet Invest 2017;82:582-591 DOI: 10.1159/000454771 590 which rest rather on the bony pelvic floor. Our dissections confirmed the presence of extravaginal spaces of relevance to surgical experimentation [10][11][12]. Given the different urethral insertion point, dissection of the ventral vaginal wall is more difficult in its lower part, yet feasible above the urethra.…”
Section: Resultssupporting
confidence: 50%
“…Those ewes display collagen metabolism changes, yet the role of estrogens remains unclear [9]. Translational researchers increasingly use this model; however, there is a need for a detailed comparative anatomical study [10][11][12]. Although anatomical descriptions of relevant pelvic structures can be found in veterinarian text books, we found they had insufficient detail for the translational and clinical researchers.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…These studies reported discordant results [17,46]. Another study in which contractility was tested, did so for the purpose of documenting the impact of foreignmaterial implantation in pelvic floor reconstruction [47]. In our sheep, we saw an increase in contractility when the ewes became reproductive and a drop at menopause.…”
Section: Discussionmentioning
confidence: 62%
“…Biologically derived materials are classed as acellular collagen matrices and are often derived from the dermis, pericardium, small intestinal submucosa or urinary bladder matrix of bovine or porcine origin [1, 22, 59]. These materials can undergo crosslinking, the formation of excessive intra- and inter-molecular bonds, to improve the longevity of the material [59].…”
Section: Materials Discussionmentioning
confidence: 99%